Non adherence to physical activity recommendations and associated factors among Type 2 Diabetic patients in Illubabor zone, South West Ethiopia - Rukiya Debalke; Beakal Zinab; Tefera Belachew (Global Journal of Obesity, Diabetes and Metabolic Syndrome - Peertechz Publications, 2022)
Introduction: Diabetic patients' poor adherence to lifestyle recommendations leads to poor glycemic control and associated micro and macro-vascular complications; however most patients have difficulty in adhering to the lifestyle modifications including physical activity recommendations.  This study assessed the magnitude of non-adherence to physical activity recommendation and associated factors among type 2 diabetic patients attending follow up at government hospitals in Ilu Abba Bora Zone, southwestern Ethiopia.  Methods: Institution based cross-sectional study was conducted from March 19 to May 19, 2018, among 422 diabetic patients attending regular follow up at government hospitals in Illuababor Zone, Southwest Ethiopia, participants were selected using systematic sampling method. Physical activity adherence was assessed using Global Physical Activity Questionnaire [GPAQ]. Multivariable logistic regression was used to identify factors associated with diabetic patients' non-adherence to physical activity recommendations.  Results: The study found that 38% of diabetic patients were non-adherent to physical activity recommendations. The odds non-adherence to physical activity recommendations was independently associated with patients' sex (AOR=2 (95%CI:1.2, 3.4)), perceived severity of the illness (AOR=1.7 (95%CI:1.1, 2.8)) and self-efficacy (AOR=2.6 (95%CI:1.6,4.4)).  Conclusion and recommendations: High proportions of diabetic patients were non-adherent to physical activity recommendations. Evidence based and Patient centered management plan should be practiced. The results imply that integrating lifestyle modification education focussing on physical activity recommendations should be integrated into diabetic care.